2004
DOI: 10.4049/jimmunol.172.10.6101
|View full text |Cite
|
Sign up to set email alerts
|

IL-9-Induced Expansion of B-1b Cells Restores Numbers but Not Function of B-1 Lymphocytes in xid Mice

Abstract: Mice expressing the X-linked immunodeficiency (xid) mutation lack functional Bruton’s tyrosine kinase and were shown to be specifically deficient in peritoneal B-1 lymphocytes. We have previously shown that IL-9, a cytokine produced by TH2 lymphocytes, promotes B-1 cell expansion in vivo. To determine whether IL-9 overexpression might compensate the xid mutation for B-1 lymphocyte development, we crossed xid mice with IL-9-transgenic mice. In this model, IL-9 restored normal numbers of mature peritoneal B-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Cell transfer studies then showed that these populations, also referred to as subsets, are developmentally distinct, in that, each is capable of fully replenishing its niche when sorted and transferred to adoptive recipients and neither has the capability to more than minimally replenish the other (2,5,6). Consistent with this developmental distinction, and with differences noted between the B-1a and B-1b repertoire, recent studies have shown that B-1a and B-1b have distinct immune functions and respond differently to antigenic stimulation (1,(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 56%
“…Cell transfer studies then showed that these populations, also referred to as subsets, are developmentally distinct, in that, each is capable of fully replenishing its niche when sorted and transferred to adoptive recipients and neither has the capability to more than minimally replenish the other (2,5,6). Consistent with this developmental distinction, and with differences noted between the B-1a and B-1b repertoire, recent studies have shown that B-1a and B-1b have distinct immune functions and respond differently to antigenic stimulation (1,(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 56%
“…Most recently, foreshadowing studies presented here, we have shown that immunization with FtL, an atypical LPS isolated from Ft LVS, induces B-1a with FtL-binding IgM receptors to appear in spleen and to produce anti-FtL IgM primary antibody responses that protect against lethal Ft LVS challenge (19,20). Consistent with B-1a mediating this protection, FtL priming does not similarly protect Bruton's tyrosine kinase (Btk)-mutant (xid) mice, which have B-1b but lack B-1a (21)(22)(23).…”
mentioning
confidence: 69%
“…B1-b cells preferentially reside in the peritoneal cavity and are characterized by expression of the Mac1 cell surface Ag. Although they share these characteristics with CD5 ϩ B1-a cells, IL-9-activated B1-b cells fail to recapitulate activities ascribed to B1-a cells, including natural IgM and autoantibody production (27,46). Interestingly, in a silica-induced lung fibrosis model, the anti-fibrotic effect of IL-9 correlated with increased B cell numbers in BAL (26) and was lost in B cell-deficient mice (47).…”
Section: Discussionmentioning
confidence: 99%